Commentary regarding parenting coordination in cases of high conflict disputes. Issue 1 (2nd January 2017) - Shaw, Morgan
ABSTRACT: There is oftentimes no distinction in disputed divorce or child custody cases between "high conflict" and "abusive" relationships. This commentary addresses the important distinction between high conflict divorce cases and cases of intimate partner violence (IPV) and highlights the differences between the two terms. It further explores the role of parenting coordination efforts in high conflict cases and how those efforts are not always appropriate in cases of abuse. There is also further discussion regarding the importance of appropriate training for parent coordinators and, at minimum, what that training should entail.